2020
DOI: 10.1002/ceas.12167
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Beginning and Expert Supervisors’ Supervision Cognitions

Abstract: Beginning and expert supervisors’ cognitions and cognitive structures were compared via concept mapping, a mixed methods design. Both beginning and expert supervisors reported a variety of cognitions representing developmental characteristics in 3 areas: assessment of supervisees, conceptualization and management of supervision, and supervisory relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 18 publications
4
6
0
1
Order By: Relevance
“…The second area appeared to highlight transitional/adaptable supervisor characteristics from counseling role to supervisory and/or educational roles, such as assessing the supervisee, using counseling skills to facilitate the supervisee's growth, and intervening accordingly. Similar to previous research findings (e.g., Kemer, 2020;Kemer et al, 2019), beginning supervisors' peer feedback indicated that being genuine with supervisees, adapting microskills and process skills from counseling, and paying attention to the needs of the supervisee and necessities of the process in any given supervision session were enhancing aspects of their peers' supervision practices. In fact, beginning supervisors' positive feedback statements also paralleled expert academe (Kemer et al, 2014) and site (Kemer et al, 2017) supervisors' supervision cognitions, encompassing intentional conceptualization and interventions of supervision practices.…”
Section: Areas Of Beginning Supervisors' Peer Feedbacksupporting
confidence: 82%
See 3 more Smart Citations
“…The second area appeared to highlight transitional/adaptable supervisor characteristics from counseling role to supervisory and/or educational roles, such as assessing the supervisee, using counseling skills to facilitate the supervisee's growth, and intervening accordingly. Similar to previous research findings (e.g., Kemer, 2020;Kemer et al, 2019), beginning supervisors' peer feedback indicated that being genuine with supervisees, adapting microskills and process skills from counseling, and paying attention to the needs of the supervisee and necessities of the process in any given supervision session were enhancing aspects of their peers' supervision practices. In fact, beginning supervisors' positive feedback statements also paralleled expert academe (Kemer et al, 2014) and site (Kemer et al, 2017) supervisors' supervision cognitions, encompassing intentional conceptualization and interventions of supervision practices.…”
Section: Areas Of Beginning Supervisors' Peer Feedbacksupporting
confidence: 82%
“…Beginning supervisors' feedback on process and immediacy in their peers' sessions included both positive and constructive feedback. Thus, supporting Kemer's (2020) findings from a developmental lens, our beginning supervisors' feedback on process and immediacy was mainly focused on their peers' challenges with balancing tasks and process of supervision. Supervisor presence, flexibility, and collaboration, as well as attendance to the process of supervisory work (e.g., too much or too little task focus, lack of attention to supervisee's personal experiences influencing the counseling work or power struggles between supervisee and supervisor) were reported as the hindering aspects of beginning supervisors' supervision practices.…”
Section: Developmental Characteristics In Peer Feedback Categories Of Beginning Supervisorssupporting
confidence: 68%
See 2 more Smart Citations
“…Es aquí donde los mapas conceptuales utilizados intencionalmente por docentes pueden evidenciar, como señalan Sellman, Liefländer y Bogner (2015), ideas que ya han construido sus estudiantes, también los progresos en el entendimiento conceptual y, por consiguiente, en el aprendizaje significativo de un concepto (Gardner, Lohr, Bartos y Reid, 2019;Kemer, 2020;Ceylan, y Atabek, 2018), o utilizarse incluso como estrategias de adquisición de conocimiento (Olivo, 2017).…”
Section: Introductionunclassified